The need to accessorize: molecular roles of HTLV-1 p30 and HTLV-2 p28 accessory proteins in the viral life cycle - Anupam, Rajaneesh; Doueiri, Rami; Green, Patrick L. (Frontiers in Microbiology, 2013)
Extensive studies of HTLV-1 and HTLV-2 over the last three decades have provided detailed knowledge on viral transformation, host-viral interactions and pathogenesis. HTLV-1 is the etiological agent of adult T cell leukemia (ATL) and multiple neurodegenerative and inflammatory diseases while HTLV-2 disease association remains elusive, with few infected individuals displaying neurodegenerative diseases similar to HTLV-1. The HTLV group of oncoretroviruses has a genome that encodes structural and enzymatic proteins Gag, Pro and Env, regulatory proteins Tax and Rex, and several accessory proteins from the pX region. Of these proteins, HTLV-1 p30 and HTLV-2 p28 are encoded by the open reading frame (ORF) II of the pX region. Like most other accessory proteins, p30 and p28 are dispensable for in vitro viral replication and transformation but are required for efficient viral replication and persistence in vivo. Both p30 and p28 regulate viral gene expression at the post-transcriptional level whereas p30 can also function at the transcriptional level. Recently, several reports have implicated p30 and p28 in multiple cellular processes, which provide novel insight into HTLV spread and survival and ultimately pathogenesis. In this review we summarize and compare what is known about p30 and p28, highlighting their roles in viral replication and viral pathogenesis.